Peningkatan Profesionalisme Guru melalui Workshop Penyusunan Penelitian Tindakan Kelas dan Publikasi Artikel Ilmiah - Myori, Dwiprima Elvanny; Asnil, Asnil; Dewi, Citra; Yanto, Doni Tri Putra (Jurnal Pendidikan Teknik Elektro, 2024)
Region VII Education Authorities of West Sumatera is working hard to improve the competence and professionalism of teachers in enriching knowledge through Classroom Action Research (CAR) and publication of scientific articles. The goal is to have quality teachers, then quality education will also be created. Based on the results of observations and interviews conducted with the Regional VII Education Authorities, the problem faced is regarding the insufficient number of teachers who have published scientific articles. Based on the problems faced, one of the things that can be done in solving the problem is to conduct workshops on the preparation of CAR and publication of scientific articles as an effort to increase the professionalism of teachers in Region VII. The purpose of this activity is to create quality education through qualified teachers. The methods used in this activity are lectures, demonstrations and practice. Data collection techniques as data on the results of the implementation of this activity using questionnaires and activity documentation. The results obtained from this training are increased competency of vocational teachers in designing CAR and scientific articles as evidenced by increased teacher knowledge in implementing CAR and writing scientific articles. This was obtained through the results of the questionnaire analysis given to the participants after the training. Through this activity it is hoped that it can assist the Education Authorities in improving the quality of education, especially for SMK teachers in Region VII. Through this activity it is also hoped that several draft CAR proposals and scientific article drafts will be produced which are the work of the activity participants. The results of this activity will later be applied directly by the participants in their respective schools.